The Impact of Agricultural Productivity on Economic Growth in Africa - Maiga, Yohana (Journal of Agricultural Studies, 2024)
This study investigates the relationship between agricultural productivity and economic growth in five African countries: Tanzania, Ghana, Kenya, Morocco, and South Africa. Secondary data from reputable sources are analyzed using statistical tests and regression models. The findings indicate that agriculture significantly contributes to Africa’s economic growth. South Africa exhibits the highest agricultural productivity, followed by Morocco, Kenya, Ghana, and Tanzania. However, despite their agricultural strengths, South Africa and Morocco have relatively lower contributions to economic growth due to other factors like low employment rates. Ghana and Kenya show comparable performance, while Tanzania lags behind despite experiencing economic growth and having a high employment rate. It is emphasized that economic growth is influenced by various factors beyond agriculture, and countries with high agricultural productivity should diversify their economies and address other determinants of growth. Policy measures to strengthen the agricultural sector and promote diversification are crucial for sustainable economic development in Africa.